2017
DOI: 10.1126/science.aan4497
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the redox switches in the NAD + -reducing soluble [NiFe]-hydrogenase

Abstract: NAD (oxidized form of NAD:nicotinamide adenine dinucleotide)-reducing soluble [NiFe]-hydrogenase (SH) is phylogenetically related to NADH (reduced form of NAD):quinone oxidoreductase (complex I), but the geometrical arrangements of the subunits and Fe-S clusters are unclear. Here, we describe the crystal structures of SH in the oxidized and reduced states. The cluster arrangement is similar to that of complex I, but the subunits orientation is not, which supports the hypothesis that subunits evolved as prebuil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 40 publications
4
59
2
Order By: Relevance
“…The first heterogeneous catalysts for HER are based on “host–guest” structures where single metal centers are hosted on the surface of conductive carbon materials by covalent or noncovalent bonds . In a recent study, inspired by hydrogenases, nickel bisdiphosphine was assembled onto CNT surfaces, which exhibited high catalytic activity toward HER, with an onset potential of only −20 mV and almost unchanged current density after continuous operation for 10 h. In another study, a hybrid of ploy(cobaloxime) and CNTs was prepared by π–π interactions between CNTs and the pyrene moiety which was tethered to ploy(cobaloxime). The hybrid catalyst possessed an apparent activity toward HER at near‐neutral pH, with the cobalt‐based turnover number up to 420, about four times higher than that of monomeric cobaloxime.…”
Section: Electrocatalytic Performancementioning
confidence: 99%
“…The first heterogeneous catalysts for HER are based on “host–guest” structures where single metal centers are hosted on the surface of conductive carbon materials by covalent or noncovalent bonds . In a recent study, inspired by hydrogenases, nickel bisdiphosphine was assembled onto CNT surfaces, which exhibited high catalytic activity toward HER, with an onset potential of only −20 mV and almost unchanged current density after continuous operation for 10 h. In another study, a hybrid of ploy(cobaloxime) and CNTs was prepared by π–π interactions between CNTs and the pyrene moiety which was tethered to ploy(cobaloxime). The hybrid catalyst possessed an apparent activity toward HER at near‐neutral pH, with the cobalt‐based turnover number up to 420, about four times higher than that of monomeric cobaloxime.…”
Section: Electrocatalytic Performancementioning
confidence: 99%
“…21 In addition, it has recently been reported that Ni in the active site of NAD + -reducing [NiFe]-hydrogenase (Group 3d) in the AOXI state is coordinated by the nearby glutamate that would protect O 2 access. 22 We propose a novel molecular mechanism for protecting the active site from O 2 damage in S77HYB (Fig. S8, ESI †).…”
Section: +mentioning
confidence: 99%
“…Because FdsB-and FdsG-like domains are found in all members of the NADH dehydrogenase superfamily (12,14), we have undertaken a study of the FdsBG subcomplex of C. necator formate dehydrogenase, with the aim of putting the oxidative half-reaction of the enzyme in a structural context. Here, we present the structure of FdsBG complex and characterize its kinetic properties.…”
mentioning
confidence: 99%